How to Solve Problems in Dictionary Use: The Georgian Case - Margalitadze, Tinatin; Meladze, George (Lexikos, 2023)
The present article was inspired by the plenary lecture given by Rufus Gouws at the XX International Congress of EURALEX in Mannheim: "Dictionaries: Bridges, Dykes, Sluice Gates" (Gouws 2022). His emphasis on the lack of a dictionary culture and the responsibilities that not only lexicography has towards society, but that society also has towards lexicography is an important perspective that is relevant for many societies, including Georgian society. While Gouws uses this term as an umbrella term to refer to both the user-friendliness of dictionaries, on the one hand, and the ability and willingness of society to use dictionaries and their knowledge of dictionary-use skills, on the other, in the present article we concentrate more on the latter aspect of the term dictionary culture. Numerous studies conducted in the field of dictionary use since the 1970s have revealed that many users did not know how to use dictionaries, were not familiar with the structure of entries, could not identify what part of speech this or that word was, had no idea of homonymy, polysemy and related issues; this led to errors in comprehension, translation and other tasks related to foreign language acquisition. These studies, conducted in different countries, also clearly showed the need to teach dictionary use in schools and universities. Unfortunately, despite efforts from lexicographers and educators to improve this situation, and despite some positive steps taken in this direction which will be discussed in the paper, there is still no satisfactory teaching of dictionary use in educational institutions that would help create or sustain dictionary culture. The aim of this article is to discuss problems in dictionary use in the Georgian context and share our experience of introducing the teaching of lexicography and developing dictionary-use skills at Georgian universities. Keywords: dictionary culture, teaching dictionary use, dictionary use skills, exercises, dictionary didactics, English–Georgian dictionary